Português: Português (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
This study aims to present and differentiate the essential concepts related to the idea of development, starting from the notion of growth, all the way to the idea of sustainable development. Notwithstanding the literature that has already specifically studied the many concepts related to the notion of development, this study differentiates those terms, so as to contribute towards a scenario of better clarity and conceptual refinement. Therefore, the goal is to prevent common misunderstandings, which commonly associate these ideas to related concepts, terms, or phenomena, especially in the face of the variety of possible meanings that the word development can encompass. In conclusion, there is the contribution of a perspective around the key concepts related to the notion of development.